2022
DOI: 10.1038/s41598-022-25871-2
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing of immune cells in patients with acute gout

Abstract: Cell subpopulations in the blood and joint fluid of patients with gout are poorly understood. Single-cell RNA sequencing and bioinformatic tools were used to identify cell subsets and their gene signatures in blood and synovial fluid (SF) cells, determine their relationships, characterize the diversity, and evaluate interactions among specific cell types. We identified 34 subpopulations (5 types of B cells, 16 types of T and natural killer cells, 9 types of monocytes, and 4 other cell types) in the blood of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In gout, MSU crystals stimulate the macrophage by activating NLRP3 inflammasome, triggering the release of pro-inflammatory cytokines [ 10 , 34 ]. Although IL-1β plays a crucial role in the pathogenesis of the pathogenesis of gout flares, other cytokines such as IL-6, TNF-α, and TGF-β are also involved in that [ 16 , 31 , 35 ]. In the present study, the IL-6 levels were elevated in gout patients, and positively related to ESR, CRP, D-dimer, fibrinogen, neutrophils and monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gout, MSU crystals stimulate the macrophage by activating NLRP3 inflammasome, triggering the release of pro-inflammatory cytokines [ 10 , 34 ]. Although IL-1β plays a crucial role in the pathogenesis of the pathogenesis of gout flares, other cytokines such as IL-6, TNF-α, and TGF-β are also involved in that [ 16 , 31 , 35 ]. In the present study, the IL-6 levels were elevated in gout patients, and positively related to ESR, CRP, D-dimer, fibrinogen, neutrophils and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curves showed that disease duration, CRP and fibrinogen had moderate predictive performances for tophus in gout, which indicated that tophus was chronic inflammatory tissue response and mostly the result of chronic recurrent gout attacks [ 48 ]. Further studies with the aid of single-cell RNA sequencing and other advanced new technologies may accurately explore the Th17/Treg imbalance in different disease states of gout [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have examined single-cell–level differences in peripheral blood immune cells between patients with gout flares and healthy individuals ( 23 , 24 ). However, our work focused on investigating the gradual shift in the landscape of such cells during the transitional stages from gout flares to remission, which we believe offers valuable insights with considerable clinical therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…In other forms of arthritis, such as ankylosing spondylitis, gout, and psoriasis arthritis, increased frequencies of MAIT cells in the inflamed joints have been observed, while peripheral MAIT cell numbers are generally reduced and show an exhausted phenotype [96,[103][104][105]. Similar to RA, blood MAIT cells may infiltrate the joints via the CCR6/CCL20 and CXCR6/CXCL16 axis [95], upregulate IL-23R, and produce IL-17 in the synovia [96,97,103,104].…”
Section: Ankylosing Spondylitis Psoriasis Arthritis and Goutmentioning
confidence: 99%